RURAL LANDSCAPES AND HUMAN PRESSURE IN THE SUBCARPATHIAN DEPRESSIONS OF OLTENIA. GEOGRAPHICAL CONSIDERATIONS - MIHAELA RODICA PERSU; DANIELA VIOLETA NANCU (Revue Roumaine de Géographie)
The rural landscape has been moderately changed by human intervention in the natural space. The country-side has the capacity to preserve and reconstruct the natural landscape because human pressure isless severe than in the urban area. What has an impact on the former is the concentration and dispersion of population and of land, as well as other economic activities that affect the environment. In order to single out the types of rural landscape, our analysis has focused on the distinct territorial traits of villages and villagehearths, population dynamics land-use practices, and anthropogenic grade. The present case-study looks at the structure and territorial distribution of rural landscape types in the Subcarpathian depressions of Oltenia and man’s overuse of the natural background.